Examinando el desplazamiento horizontal de la pared del diafragma abrazada por el puntal afectado por cimientos apilados adyacentes a excavaciones profundas urbanas - Darvishpour, Alireza; Amiri, Amirmohammad; Ranjbar, Asadollah (Innovaciencia, 2019)
Utilizing the piled foundation is extremely important and applicable in the civil and geotechnical engineering due to the improvementin the bearing capacity. Employing urban deep excavations, on the other hand, is inevitable and examining the effect of the pile groupis significantly vital due to the nearness of adjacent structures. In this research, the effect of the pile group foundation on the diaphragm wall embraced with struts in urban deep excavations is examined using two-dimensional numerical modeling. The resultsobtained from modeling show that the horizontal distance between the foundation and the excavation edge and also the pile lengthcan significantly affect the horizontal displacement of the wall and the moment diagram imposed on the wall, so that the effect ofthe foundation on the wall is considerably reduced for the distance greater than a certain value.